2015
DOI: 10.18632/oncotarget.3763
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of Akirin-2 increases chemosensitivity in human glioblastomas more efficiently than Twist-1

Abstract: The Twist-1 transcription factor and its interacting protein Akirin-2 regulate apoptosis. We found that in glioblastomas, highly malignant brain tumors, Akirin-2 and Twist-1 were expressed in glial fibrillary acidic protein positive tumor regions as well as in tumor endothelial cells and infiltrating macrophages / microglia. Temozolomide (TMZ) induced the expression of both molecules, partly shifting their nuclear to cytosolic localization. The knock-down (kd) of Akirin-2 increased the activity of cleaved (c)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…Subolesin/Akirin are also involved in the Relish/NF-kB independent gene regulation (Figure 4 ), thus playing a role in various biological processes in addition to the immune response (Figure 5 ). These processes include animal reproduction and development, causing lethal embryonic or reduced growth phenotypes in knockout mice, fruit fly, ticks, and nematodes ( Maeda et al, 2001 ; de la Fuente et al, 2006a ; Goto et al, 2008 ; Carpio et al, 2013 ; Qu et al, 2014 ), metazoan myogenesis ( Marshall et al, 2008 ; Salerno et al, 2009 ; Macqueen et al, 2010a ; Mobley et al, 2014 ; Sun et al, 2016 ), Xenopus neural development ( Liu et al, 2017 ), meiosis/carcinogenesis ( Komiya et al, 2008 ; Macqueen et al, 2010b ; Clemons et al, 2013 ), tick stress response, feeding, growth and reproduction ( Almazán et al, 2003 , 2005 ; de la Fuente et al, 2006a , 2008 ; Smith et al, 2009 ; Busby et al, 2012 ; Rahman et al, 2018 ), pathogen infection and transmission in ticks ( de la Fuente et al, 2006b , 2016 , 2017a ; Zivkovic et al, 2010a , b ; Busby et al, 2012 ; Hajdušek et al, 2013 ) and turbot ( Yang et al, 2011 ), human glioblastoma cell apoptosis ( Krossa et al, 2015 ), cattle marbling ( Sasaki et al, 2009 ; Watanabe et al, 2011 ; Kim et al, 2013 ), and mouse mitogen-induced B cell cycle progression and humoral immune responses ( Tartey et al, 2015 ). For example, as previously reported in I. scapularis and other tick species ( de la Fuente and Kocan, 2006 ; de la Fuente et al, 2006a , b , 2011 , 2013 ; Merino et al, 2013a ; de la Fuente and Contreras, 2015 ), Subolesin appears to function in multiple biological processes such as tick response to infection, feeding, reproduction, development and stress response (Figure 6 ).…”
Section: Function Of Subolesin/akirinmentioning
confidence: 99%
“…Subolesin/Akirin are also involved in the Relish/NF-kB independent gene regulation (Figure 4 ), thus playing a role in various biological processes in addition to the immune response (Figure 5 ). These processes include animal reproduction and development, causing lethal embryonic or reduced growth phenotypes in knockout mice, fruit fly, ticks, and nematodes ( Maeda et al, 2001 ; de la Fuente et al, 2006a ; Goto et al, 2008 ; Carpio et al, 2013 ; Qu et al, 2014 ), metazoan myogenesis ( Marshall et al, 2008 ; Salerno et al, 2009 ; Macqueen et al, 2010a ; Mobley et al, 2014 ; Sun et al, 2016 ), Xenopus neural development ( Liu et al, 2017 ), meiosis/carcinogenesis ( Komiya et al, 2008 ; Macqueen et al, 2010b ; Clemons et al, 2013 ), tick stress response, feeding, growth and reproduction ( Almazán et al, 2003 , 2005 ; de la Fuente et al, 2006a , 2008 ; Smith et al, 2009 ; Busby et al, 2012 ; Rahman et al, 2018 ), pathogen infection and transmission in ticks ( de la Fuente et al, 2006b , 2016 , 2017a ; Zivkovic et al, 2010a , b ; Busby et al, 2012 ; Hajdušek et al, 2013 ) and turbot ( Yang et al, 2011 ), human glioblastoma cell apoptosis ( Krossa et al, 2015 ), cattle marbling ( Sasaki et al, 2009 ; Watanabe et al, 2011 ; Kim et al, 2013 ), and mouse mitogen-induced B cell cycle progression and humoral immune responses ( Tartey et al, 2015 ). For example, as previously reported in I. scapularis and other tick species ( de la Fuente and Kocan, 2006 ; de la Fuente et al, 2006a , b , 2011 , 2013 ; Merino et al, 2013a ; de la Fuente and Contreras, 2015 ), Subolesin appears to function in multiple biological processes such as tick response to infection, feeding, reproduction, development and stress response (Figure 6 ).…”
Section: Function Of Subolesin/akirinmentioning
confidence: 99%
“…Mechanistically, this is attributed to the increased migratory and invasive capacities of glioma cells by TWIST1 activity [ 56 ]. Additionally, TWIST1 expression has been associated with resistance of glioblastoma cells to temozolomide [ 57 ]. Importantly, one study found that a reduction of TWIST1 expression in glioma stem cells, achieved by co-culturing these stem cells with mesenchymal stem cells, induces a mesenchymal-to-epithelial transition (MET), the inverse process of EMT, in these cells [ 58 ].…”
Section: Transcription Factors Involved In the Mesenchymal Transitionmentioning
confidence: 99%
“…Akirin2 is overexpressed in a number of tumor cell lines, and antisense-mediated knockdown of Akirin2 led to growth inhibition and reduced tumorigenicity and metastasis of K2 hepatoma and Lewis lung carcinoma cell lines [13, 18]. Akirin2 knockdown also renders glioblastoma cell lines more prone to cell death, suggesting that Akirin2 is important for cell survival in rapidly dividing cells [19]. …”
Section: Introductionmentioning
confidence: 99%